2013
DOI: 10.1074/jbc.m112.437889
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of the Cytotoxicity of Human α-Lactalbumin Made Lethal to Tumor Cells (HAMLET) and Other Protein-Oleic Acid Complexes

Abstract: Background:The ␣-lactalbumin-oleic acid complex has a unique apoptotic activity for selectively killing tumor cells. Results: We identified the oleic acid-binding site in the human-and goat-␣-lactalbumin complexes by two-dimensional NMR. Conclusion: Oleic acid is bound to a loosely organized hydrophobic core of the proteins in the molten globule state. Significance: The results are crucial for understanding the molecular mechanisms of the cytotoxicity of the protein-oleic acid complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 63 publications
2
36
0
2
Order By: Relevance
“…The protein-OA complexes are prepared from bovine -lactalbumin (BLA, BAMLET) 1 , equine lysozyme (EL, ELOA) 2 , goat -lactalbumin (GLA, GAMLET) 9 and other proteins that are made to bind OA using a variety of approaches, including passage of the protein through a column equilibrated with OA 2; 4 , direct titration of OA into a protein solution 3; 10 , and heat treatment 9; 11 . HAMLET was initially thought to consist of one, or only a few, oleic acids initially described as "cofactors" 12 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The protein-OA complexes are prepared from bovine -lactalbumin (BLA, BAMLET) 1 , equine lysozyme (EL, ELOA) 2 , goat -lactalbumin (GLA, GAMLET) 9 and other proteins that are made to bind OA using a variety of approaches, including passage of the protein through a column equilibrated with OA 2; 4 , direct titration of OA into a protein solution 3; 10 , and heat treatment 9; 11 . HAMLET was initially thought to consist of one, or only a few, oleic acids initially described as "cofactors" 12 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The mechanism of the antitumor activity of HAMLET (human α-lactalbumin made lethal to tumor cells)-like complexes has been studied extensively (Hallgren et al, 2006;Aits et al, 2009;Zhang et al, 2013), and the toxicity of these complexes has been reported to be highly dependent on OA (Brinkmann et al, 2011;Nakamura et al, 2013). Furthermore, the antitumor properties of OA have been widely acknowledged (Brinkmann et al, 2011;Carrillo et al, 2012;Hoque et al, 2013;Fang et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…In addition, intact milk proteins have been associated with a wide range of in vitrobioactivities, such as satiating, antimicrobial, mineral binding, anti-lipidaemic and anticancer properties [2,28,30,93]. During digestion in humans, milk proteins are cleaved by various proteinases and peptidases in the gastrointestinal tract (GIT), resulting in the generation of free amino acids and peptides [131].…”
Section: Introductionmentioning
confidence: 99%